A MAS-Based Cloud Service Brokering System to Respond Security Needs of Cloud Customers - Talbi, Jamal; Haqiq, Abdelkrim (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Cloud computing is becoming a key factor in computer science and an important technology for many organizations to deliver different types of services. The companies which provide services to customers are called as cloud service providers. The cloud users (CUs) increase and require secure, reliable and trustworthy cloud service providers (CSPs) from the market. So, it’s a challenge for a new customer to choose the highly secure provider. This paper presents a cloud service brokering system in order to analyze and rank the secured cloud service provider among the available providers list. This model uses an autonomous and flexible agent in multi-agent system (MASs) that have an intelligent behavior and suitable tools for helping the brokering system to assess the security risks for the group of cloud providers which make decision of the more secured provider and justify the business needs of users in terms of security and reliability.
Keywords: security; multi-Agent systems; risk; cloud computing; IJIMAI